Evaluating the Risk of Hypertension, Fatigue, Sleeping Disorders, and Back or Neck Symptoms in 41,277 Low-Fit Workers With Varying Occupational Physical Activity (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: To study whether the risk of hypertension and perceived health symptoms increases with increased occupational physical activity (OPA) among low-fit individuals in low-skilled occupations.Methods: Data from a total of 41,277 individuals (mean age 46, standard deviation ±11, years; 55% women) who underwent occupational health profile assessments in Sweden between 1988 and 2020 were included. Individuals were selected from nine occupational groups (according to SSYK/ISCO classification) with generally low educational requirements, containing ‘office assistants’, ‘mobile plant operators and vehicle drivers’, ‘shop staff’, ‘heavy truck and lorry drivers’, ‘assemblers, machine operators, and related’, ‘assistant nurses and home care’, ‘cleaners’, ‘construction craftsmen and related trades’, and ‘construction workers’ (presented with increased OPA, defined in PMID:38129646). Fitness (V̇O₂max) was estimated by a submaximal cycle test, and low-fit was defined as